2006
DOI: 10.1681/asn.2006070798
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Nitric Oxide Synthase Deficiency Produces Accelerated Nephropathy in Diabetic Mice

Abstract: Functionally significant polymorphisms in endothelial nitric oxide synthase (eNOS) and reduced vascular eNOS activity have been associated with increased human diabetic nephropathy (DN), but the pathogenic role of eNOS deficiency in the development of DN has not yet been confirmed. This study characterizes the severity of DN in eNOS ؊/؊ mice that were backcrossed to C57BLKS/J db/db mice. Although the severity of hyperglycemia was similar to C57BLKS/J db/db mice, by 26 wk, eNOS ؊/؊ C57BLKS/J db/db mice exhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
328
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 327 publications
(354 citation statements)
references
References 44 publications
24
328
2
Order By: Relevance
“…30,31 In diabetic lepr db/db mice, deficiency of eNOS resulted in accelerated nephropathy with mesangiolysis and early nodular lesions at 26 weeks. 32 However, in the later fasttrack report, limited to renal studies, the authors neither described endothelial injury, significant tubulointerstitial damage nor provided substantial quantitative analysis.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 In diabetic lepr db/db mice, deficiency of eNOS resulted in accelerated nephropathy with mesangiolysis and early nodular lesions at 26 weeks. 32 However, in the later fasttrack report, limited to renal studies, the authors neither described endothelial injury, significant tubulointerstitial damage nor provided substantial quantitative analysis.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon may facilitate the progression of nephropathy in a manner similar to the manner seen in eNOS 2/2 mice: diabetic nephropathy is exacerbated in conjunction with a moderate increase in systolic BP, leading to a more progressive renal phenotype, including tubulointerstitial fibrosis. [50][51][52][53] Podocyte-expressing Nox5 mice exhibit early increases in systolic BP accompanied by progressive tubulointerstitial fibrosis. Although the exact mechanism that elevates BP remains unclear, it is possible that increased superoxide production resulting from aberrant Nox5 activity may lead to decreased NO bioavailability, with consequent decreased vasodilation and increased vascular resistance and elevation of systolic BP.…”
Section: Discussionmentioning
confidence: 99%
“…The field of vascular research in DN received a substantial boost in 2006 and 2007 when two groups reported in JASN that diabetic mice null for endothelial nitric oxide synthase (eNOS2/2) recapitulated major structural and functional features of advanced human DN. 2,3 The enzyme eNOS is highly specifically expressed in the endothelium and is responsible for producing the vasodilator nitric oxide, which is thought to contribute to vascular homeostasis. Loss of eNOS-derived nitric oxide activity has been observed in diabetic patients well before the onset of severe end-organ complications (reviewed by De Vriese et al 4 ).…”
mentioning
confidence: 99%